The effects of maternity waiting homes on the health workforce and maternal health service delivery in rural Zambia: a qualitative analysis - Jeanette L. Kaiser; Rachel M. Fong; Thandiwe Ngoma; Kathleen Lucile McGlasson; Godfrey Biemba; Davidson H. Hamer; Misheck Bwalya; Maynards Chasaya; Nancy A. Scott (BMC, 2019)
Abstract Background Maternity waiting homes (MWHs) are a potential strategy to address low facility delivery rates resulting from access-associated barriers in resource-limited settings. Within a cluster-randomized controlled trial testing a community-generated MWH model in rural Zambia, we qualitatively assessed how MWHs affect the health workforce and maternal health service delivery at their associated rural health centers. Methods Four rounds of in-depth interviews with district health staff (n = 21) and health center staff (n = 73) were conducted at intervention and control sites over 24 months. We conducted a content analysis using a mixed inductive-deductive approach. Data were interpreted through the lens of the World Health Organzation Health Systems Framework. Results Nearly all respondents expressed challenges with understaffing and overwork and reported that increasing numbers of facility-based deliveries driven by MWHs contributed substantively to their workload. Women waiting at MWHs allow staff to monitor a woman's final stage of pregnancy and labor onset, detect complications earlier, and either more confidently manage those complications at the health center or refer to higher level care. District, intervention, and control site respondents passionately discussed this benefit over all time points, describing it as outweighing challenges of additional work associated with MWHs. Intervention site staff repeatedly discussed the benefit of MWHs in providing a space for postpartum women to wait after the first few hours of clinical observation through the first 48 h after delivery. Additionally, intervention site staff perceived the ability to observe women for longer before and after delivery allowed them to better anticipate and plan their own work, adjust their workloads and mindset accordingly, and provide better and more timely care. When understaffing and overwork were frequently discussed, this satisfaction in providing better care was a meaningful departure. Conclusions MWHs may benefit staff at rural health centers and the health system more broadly, allowing for the provision of more timely and comprehensive obstetric care. We recommend future studies consider how MWHs impact the workforce, operations, and service delivery at their associated health facilities. Considering the limited numbers of skilled birth attendants available in rural Zambia, it is important to strategically select locations for new MWHs. Trial registration Clinicaltrials.gov, NCT02620436. Registered December 3, 2015, https://clinicaltrials.gov/ct2/show/NCT02620436